Advanced application of bovine intestinal epithelial cell line for evaluating regulatory effect of lactobacilli against heat-killed enterotoxigenicEscherichia coli-mediated inflammation - Takanashi, Naoya (2013)
Background: Previously, a bovine intestinal epithelial cell line (BIE cells) was successfully established. This work hypothesized that BIE cells are useful in vitro model system for the study of interactions of microbial- or pathogenassociated molecular patterns (MAMPs or PAMPs) with bovine intestinal epithelial cells and for the selection of immunoregulatory lactic acid bacteria (LAB). Results: All toll-like receptor (TLR) genes were expressed in BIE cells, being TLR4 one of the most strongly expressed. We demonstrated that heat-stable PAMPs of enterotoxigenic Escherichia coli (ETEC) significantly enhanced the production of IL-6, IL-8, IL-1! and MCP-1 in BIE cells by activating both NF-"B and MAPK pathways. We evaluated the capacity of several lactobacilli strains to modulate heat-stable ETEC PAMPs-mediated inflammatory response in BIE cells. Among these strains evaluated, Lactobacillus casei OLL2768 attenuated heat-stable ETEC PAMPs-induced pro-inflammatory response by inhibiting NF-"B and p38 signaling pathways in BIE cells. Moreover, L. casei OLL2768 negatively regulated TLR4 signaling in BIE cells by up-regulating Toll interacting protein (Tollip) and B-cell lymphoma 3-encoded protein (Bcl-3). Conclusions: BIE cells are suitable for the selection of immunoregulatory LAB and for studying the mechanisms involved in the protective activity of immunobiotics against pathogen-induced inflammatory damage. In addition, we showed that L. casei OLL2768 functionally modulate the bovine intestinal epithelium by attenuating heat-stable ETEC PAMPs-induced inflammation. Therefore L. casei OLL2768 is a good candidate for in vivo studying the protective effect of LAB against intestinal inflammatory damage induced by ETEC infection or heat-stable ETEC PAMPs challenge in the bovine host.